2019
DOI: 10.1055/a-0885-1826
|View full text |Cite
|
Sign up to set email alerts
|

In vitro-Exposition des Shisha-Tabak-Bestandteils Glycerin an humanen Mukosazellen und Lymphozyten

Abstract: ZusammenfassungShisha-Tabak benötigt im Vergleich zur Zigarette höhere Konzentrationen des Feuchthaltemittels Glycerin. Seit Mai 2016 ist die bis dahin gültige Limitierung von Feuchthaltemitteln in Tabak auf 5 % aufgehoben. Derzeit ist das toxikologische Profil des Glycerins jedoch noch nicht hinreichend erforscht.Ziel dieser Arbeit war es, Glycerin auf mögliche zyto- und genotoxische Effekte zu untersuchen, um so das Gefährdungspo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
0
1
0
1
Order By: Relevance
“…This observation corroborates previous studies that investigated the effect of different storage conditions on the microbial diversity of commercial cigarettes (Chopyk et al 2017b ), little cigars (Smyth et al 2019 ), and research cigarettes (Chattopadhyay et al 2021 ). Previous studies have also shown that, unlike other tobacco products, hookah products contain higher levels of humectants like glycerol and honey (Khater et al 2008 ; Uebelacker et al 2019 ), both of which also exhibit bacteriostatic and bactericidal activities, which could help explain the lack of effect of incubation temperatures or humidity levels on hookah tobacco alpha-diversity.…”
Section: Discussionmentioning
confidence: 99%
“…This observation corroborates previous studies that investigated the effect of different storage conditions on the microbial diversity of commercial cigarettes (Chopyk et al 2017b ), little cigars (Smyth et al 2019 ), and research cigarettes (Chattopadhyay et al 2021 ). Previous studies have also shown that, unlike other tobacco products, hookah products contain higher levels of humectants like glycerol and honey (Khater et al 2008 ; Uebelacker et al 2019 ), both of which also exhibit bacteriostatic and bactericidal activities, which could help explain the lack of effect of incubation temperatures or humidity levels on hookah tobacco alpha-diversity.…”
Section: Discussionmentioning
confidence: 99%
“…Der Stoff Glycerin wurde bereits in unsrer eigenen Arbeitsgruppe hinsichtlich seiner Toxizität als Feuchthaltemittel von Shisha-Tabak untersucht. Dabei konnten geno-und zytotoxische Effekte in Invitro-Studien beobachtet werden [31].…”
unclassified